Death Due to Brain Damage Caused by Maxillofacial Injury by Cutting-Piercing Device: A Case Report - Yaşar Teke, Hacer; Birincioğlu, İsmail; Can, Muhammed; Kurtaş, Ömer (The Bulletin of Legal Medicine, 2019)
The aim of this study is to discuss a rare case of death in the light of the literature, due to brain tissue damage and cerebral hemorrhage caused by a stab wound injury, accompanied by bone fractures in the skull. A 32-year-old male who was injured by a stab wound from the face during a discussion in a hotel was hospitalized for treatment. Cranial tomography revealed a fracture in the ethmoid bone at the anterior and lateral wall of the left maxillary sinus and ventricular hemorrhage. He died in the following day in the university hospital where he was referred. In the autopsy, a 3.5 cm long oblique stab wound incision was observed below the left eye-on the left side of the nose and just below this lesion another 0.5 cm long incision was also detected. Death cases due to brain damage with a stab wound are rarely encountered...
Keywords: Cutting-piercing device injury; Maxillofacial region; Murder; Forensic Medicine